Pregnancy in the Era of the Environmental Crisis: Plastic and Pollution - Antonio Ragusa; Giulia Principi; Maria Matta (IMR Press, 2022)
Objective: The environmental crisis we are experiencing is becoming a more popular topic of expert discussion and analysis. Human activity and expansion on the planet are exacerbating climate change and global warming, this, together with the increase in plastic production, and general pollution, posing a threat to our resources, supplies, and survival. This research aims to review what is known about the association between pollution and pregnancy and sensitize experts to women's education towards healthier behaviors. Mechanism: We chose to focus on the effects of the environment on fetal development and maternal health, considering various studies that highlight the potential consequences of exposure to certain environmental stressors. The paper briefly illustrates the probable mechanisms that, starting from cellular and intracellular damage, determined above all by plastics, lead to chronic activation of the immune system in response to danger and, therefore, to epigenetic modifications at the base of diseases in adulthood. Findings in Brief: We describe the effects of the main pollutants on pregnancy, with particular attention to the role of plastic. Finally, we briefly outline some individual possible solutions to this complex problem. Conclusions: In the era of environmental crisis, becoming aware of the mechanisms behind biological damage resulting from exposure to certain pollutants and plastics, especially in a period as sensitive as pregnancy, should be the driving force behind a change of direction. As physicians, this means educating our patients and recommending individual solutions to reduce the impact of contaminants to provide the best possible environment for women's and children's health, especially during the delicate period of pregnancy; but the ultimate solution is to drastically reduce global plastic production and pollution, and to recycle the plastic that is needed anyway.